The Influence of Loyalty and Work Environment on Organizational Citizenship Behavior (OCB) (Case Study at PT Bangkobakti Perdana Trijaya Pekan Tolan Labuhanbatu Selatan North Sumatra - Riki Handayani; Novrihan Leily Nasution; Aulia Indra (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to determine the effect of loyalty and work environment on organizational citizenship behavior at PT Bangkobakti Perdana Trijaya. The method used in this research is descriptive quantitative with a sample of 80 respondents. Loyalty has a positive effect on organizational citizenship behavior (OCB) of PT Bangkobakti Perdana Trijaya employees. This can be proven from the test results obtained beta coefficient value (β) 0.413 (p < 0.001). and the contribution of loyalty to organizational citizenship behavior (OCB) is (ΔR2) 0.163. The work environment has a positive effect on organizational citizenship behavior (OCB) of employees of PT Bangkobakti Perdana Trijaya. This can be proven from the test results obtained by the beta regression coefficient (β) 0.585 (p < 0, 01) and the contribution of the influence of the work environment on organizational citizenship behavior (OCB) of (ΔR2) 0.337. Loyalty and work environment have a positive effect on organizational citizenship behavior (OCB) of PT Bangkobakti Perdana Trijaya employees. This is evidenced by the results of the loyalty beta coefficient (β) 0.189 (p < 0.001) and the work environment (β) 0.504 (p < 0.001). positive effect on organizational citizenship behavior (OCB) of employees and the contribution of the influence of loyalty and work environment on organizational citizenship behavior (OCB) of (ΔR2) 0.365. So, the higher the loyalty of employees, supported by a good level of work environment, will bring up favorable OCB behaviors for the company/organization.